Operating conditions of container cars in railway trains of special formation - A. M. Brzhezovskiy; N. M. Voluyskiy (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
Abstract. The article considers main technical characteristics, indicators of dynamic qualities and parameters of braking effciency of special railway rolling stock of container cars (container transporters) intended for the transportation of radioactive materials — spent nuclear fuel. In accordance with the current regulatory documents of JSC Russian Railways, it is currently allowed forming special trains exclusively from container transporters of any one type, which is associated with the peculiarities of the technology for handling and transporting spent nuclear fuel, which is within the competence of the state corporation Rosatom. However, this signifcantly increases the timing of the delivery of special trains due to the need to wait for the readiness of transporters, due to the non-simultaneous delivery of any one type of assembly kits with spent nuclear fuel. The practice of handling has shown that the transportation of some types of spent nuclear fuel can be carried out with a combination of the transport operation, which implies the combination of various types of container transporters in one echelon, but at the same time it is necessary to correct certain regulatory documents of Russian Railways. For this purpose, at the request of the Rosatom corporation, a necessary set of experimental works was carried out. Authors presented results of control running dynamic, stationary and running braking tests of container transporters of various types, following as part of the same echelon, on the infrastructure of the Test Loop of JSC “VNIIZHT”, including when running along the frst ring track and along various combinations of turnouts along a tangent line (main) and lateral directions. It has been experimentally proved that it is possible to operate container transporters of various types as part of the same echelon in compliance with the conditions for ensuring traffc safety in accordance with the standards of dynamic qualities and braking effciency. Based on the test results, a regulatory document of JSC Russian Railways was developed — the Regulation on the conditions for joint operation of special freight cars (transporters) as part of one echelon, approved by the order of JSC Russian Railways dated July 22, 2021 No. 1591/r. components. Interstate standard, put into effect as nat. standard of the Russian Federation by order of the Federal Agency for Technical Regulation and Metrology dated March 17, 2016 No. 162-st. Moscow, Standartinform Publ., 2016, 54 p. (in Russ.).